2022
DOI: 10.1364/boe.479320
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of tissue optical properties in a wide spectral range: a review [Invited]

Abstract: A distinctive feature of this review is a critical analysis of methods and results of measurements of the optical properties of tissues in a wide spectral range from deep UV to terahertz waves. Much attention is paid to measurements of the refractive index of biological tissues and liquids, the knowledge of which is necessary for the effective application of many methods of optical imaging and diagnostics. The optical parameters of healthy and pathological tissues are presented, and the reasons for their diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 217 publications
0
9
0
Order By: Relevance
“…Mitrofanis’ group showed that the neuroprotective benefits of tPBM (670 nm) were more effective in the BALB/C strain than in the C57BL/6 strain. This could be attributed to deeper photon penetration, far into the brain from the skin in the BALB/C mice 89 , 225 . They also discovered that the neuroprotective effects of tPBM existed in the SNc region but not in the periaqueductal grey matter (PaG) and zona incerta-hypothalamus (ZI-Hyp) regions.…”
Section: Tpbm For Brain Diseasesmentioning
confidence: 99%
“…Mitrofanis’ group showed that the neuroprotective benefits of tPBM (670 nm) were more effective in the BALB/C strain than in the C57BL/6 strain. This could be attributed to deeper photon penetration, far into the brain from the skin in the BALB/C mice 89 , 225 . They also discovered that the neuroprotective effects of tPBM existed in the SNc region but not in the periaqueductal grey matter (PaG) and zona incerta-hypothalamus (ZI-Hyp) regions.…”
Section: Tpbm For Brain Diseasesmentioning
confidence: 99%
“…We used the average refractive index for all tissues for MC simulations, equal to 1.37 in the visible and near-infrared spectral ranges [32]. For more accurate estimates, it is necessary to consider the refractive indices' values for different tissue layers, their dispersion, and temperature dependencies [37,38]. Optical parameters of all tissues were calculated for each animal and then averaged by groups.…”
Section: Spectral Measurements and Calculation Of Tissue Optical Para...mentioning
confidence: 99%
“…PG and its aqueous solutions were common hyperosmotic agents in the immersion optical clearing of tissues in the visible, infrared, and even THz bands. [68][69][70] In refs. [64,71], their optical properties were studied (among other liquids), aimed at selecting the optimal agents for the tissue immersion optical clearing in the THz range.…”
Section: Cylmentioning
confidence: 99%